A STRATEGIC DIRECTIONS OF SUSTAINABLE DEVELOPMENT FOR FISHERIES SECTOR IN VIETNAM - Hoi, Nguyen Chu (Vietnam Journal of Marine Science and Technology, 2007)
Viet Nam has an advantages and potentials for fisheries economy development and fisheries activities links  closely to local community life. In the past innovated 20 years, the sector has reached to important achievements: It has been changed into a key production sector with high economic contribution; multi-class  economic component with oriented-market mechanism and contributed to poverty reduction in rural areas … However, the sector is facing with a lot of challenges in the way to sustainable development (SO): Aquatic  environments have been polluted and degraded more and more, increased diseases in aquaculture, loss of aquatic biodiversity, over-exploitation in some water bodies (especially in near-shore), destroyed relevant  ecosystems/habitats, livelihoods of the local people still not improved, fisheries management is limited in  term of policy and human qualification, the issues “fishers, fisheries and fishing ground” are still not  addressed, economic effects and competition of the fishery products are not strong and un-stained. Therefore, development of a Strategic Direcrions of Sustainable Development for Fisheries Sector in Vietnam (Draft of Agenda-21 for Fisheries Sector) has been drafted under guiding by Ministry of Fisheries.  The Agenda includes main aspects as following: conceptions of SO and sustainable fisheries in context of Vietnam; main achievements of the fisheries sector in the past 20 years and challenges/obstacles; Vietnam  future of fisheries and global fisheries outlook; SD goals for fisheries, guiding principles, strategic directions and priorities: and integration of SD of fisheries in annually/5 years investment projects and planning. The paper only presents about main aspects of the Agenda 21 for Fisheries Sector.